2021
DOI: 10.1097/iae.0000000000003095
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Intravitreal Infliximab in Behçet's Disease Active Posterior Uveitis

Abstract: Purpose: To study the safety of extended monthly intravitreal infliximab injections in patients with active posterior uveitis in Behcet's disease.Methods: This is a prospective, interventional, noncomparative, open-label, pilot study of 9 monthly intravitreal infliximab injections (1 mg/0.05 mL) for 22 eyes of 16 patients with active posterior uveitis in Behcet's disease. Control of inflammation and visual outcomes were assessed, and ocular complications were monitored during the study period.Results: Successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…The reported improvement in clinical parameters places intravitreal IFX as a promising strategy in the treatment of ocular inflammation. However, previous results differ from recent findings of severe immunological reactions and a high percentage of therapeutic failure after intravitreal administration of IFX in patients with posterior uveitis associated with Behçet’s disease [ 118 ]. Furthermore, evidence of an inflammatory reaction and a strong suggestion of retinotoxicity to intravitreal IFX were shown in a pilot safety study of patients with diabetic macular oedema or choroidal neovascularization secondary to age-related macular degeneration who failed conventional therapies [ 119 ].…”
Section: Implications Of Ocular Drug Pkcontrasting
confidence: 94%
“…The reported improvement in clinical parameters places intravitreal IFX as a promising strategy in the treatment of ocular inflammation. However, previous results differ from recent findings of severe immunological reactions and a high percentage of therapeutic failure after intravitreal administration of IFX in patients with posterior uveitis associated with Behçet’s disease [ 118 ]. Furthermore, evidence of an inflammatory reaction and a strong suggestion of retinotoxicity to intravitreal IFX were shown in a pilot safety study of patients with diabetic macular oedema or choroidal neovascularization secondary to age-related macular degeneration who failed conventional therapies [ 119 ].…”
Section: Implications Of Ocular Drug Pkcontrasting
confidence: 94%
“…Data related to the intravitreal use of anti-vascular endothelial growth factors such as bevacizumab and ranibizumab seem to be encouraging, even if still limited [ 147 , 150 , 151 ]. On the contrary, in a prospective open-label pilot study, monthly intravitreal infliximab injections (1 mg/0.05 mL) in patients with BD with active posterior uveitis were ineffective and associated with a high complication rate [ 152 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The main indication for infliximab therapy was uveitis in 137 patients (48.5%) and only 4 of them developed new manifestations of BD [54]. In an open-label study of monthly intravitreal infliximab injections, the authors reported a high ocular complication rate and failure to control BD uveitis; therefore, such an approach was not recommended [55].…”
Section: Andandmentioning
confidence: 99%